Distributed feedback semiconductor lasers - Carroll, John E.; Whiteaway, James; Plumb, Dick (Institution of Electrical Engineers, 1998)
The book has 8 chapters that are divided into parts. The first chapter is about semiconductor-diode laser and its design. The second chapter is about gain, loss and spontaneous emissions of semiconductor lasers. The third chapter is about modelling guided waves. Fourth chapter is about optical energy exchange in guides. The fifth chapter is about basic principles of lasers with distributed feedback. Sixth chapter deals with advanced distributed feedback laser design. Seventh chapter is about numerical modelling for DFB lasers and the eighth chapter deals with future devices, modelling and systems analysis.